ETUDE SEDIMENTOLOGIQUE DU TRIAS ET JURASSIQUE DU HAUT ATLAS DE MARRAKECH, MAROC : CONTRIBUTION A LA LOCALISATION DES NIVEAUX FAVORABLES A L’EXPLOITATION ARTISANALE POUR LA POTERIE - Hadach, Fatiha; Algouti, Ahmed; Algouti, Abdellah (European Scientific Journal, ESJ, 2015)
The work presented here is a contribution to the localization and characterization of favorable levels to artisanal mining for pottery by geochemical analysis of the clay samples. The macroscopic and microscopic description of the different facies identified in the study area allows the interpretation of sedimentological and structural characteristics of each facies. At the outcropping, these facies are generally marked by abundant figures desiccation and the presence of traces of biological activity, reflecting a low layer of water depositional environment under a moderate to low hydrodynamic regime. The samples analysed show a relatively similar to clay geochemistry of the region of Ourika Douar Tafza. As such, we are convinced that the results presented in this work will be useful and will provide a good orientation for the future potential developmental projects.